The skull and abdominal skeleton of Stenocercus dumerilii (Steindachner, 1867) (Reptilia: Squamata: Iguania) - Hernández-Ruz, Emil José (2010)
The objective of this study is to describe the skull and abdominal skeleton of the lizard Stenocercus dumerilii (Steindachner, 1867), with emphasis on those characters used in phylogenetic studies involving the genus Stenocercus. The peculiar shape of the head (pyramidal, with a distinct canthal-superciliary ridge that ends in a prominent postsupraciliary scale) results in part from the shape of the prefrontal and postfrontal bones, both of which bear protuberances projecting towards the orbital cavity. The postfrontal bone represents the highest point of the cranium. Contrary to what has been observed in other species of Stenocercus and in most Tropiduridae, the studied specimens of S. dumerilii presented a single pair of xiphisternal inscriptional ribs (followed by a pair of posterior xiphisternal processes). Besides, they presented five pairs of postxiphisternal inscriptional ribs widely separated ventrally. One specimen (of two studied) showed the pineal foramen completely enclosed by the frontal instead of in frontoparietal suture.